2011
DOI: 10.1007/s10029-011-0885-y
|View full text |Cite
|
Sign up to set email alerts
|

Three-year results from a preclinical implantation study of a long-term resorbable surgical mesh with time-dependent mechanical characteristics

Abstract: PurposeThe purpose of this study was to evaluate the biocompatibility, local tissue effects and performance of a synthetic long-term resorbable test mesh (TIGR® Matrix Surgical Mesh) compared to a non-resorbable polypropylene control mesh following implantation in a sheep model.MethodsFull-thickness abdominal wall defects were created in 14 sheep and subsequently repaired using test or control meshes. Sacrifices were made at 4, 9, 15, 24 and 36 months and results in terms of macroscopic observations, histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 22 publications
3
89
0
1
Order By: Relevance
“…The knitted structure of TIGR ® Matrix allows for easy handling and fixation while being strong and flexible. As shown in preclinical trials, it is rapidly vascularized, has a transient inflammatory response, and, over time, is replaced by well-organized connective tissue [18]. This was also our observation during this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The knitted structure of TIGR ® Matrix allows for easy handling and fixation while being strong and flexible. As shown in preclinical trials, it is rapidly vascularized, has a transient inflammatory response, and, over time, is replaced by well-organized connective tissue [18]. This was also our observation during this study.…”
Section: Discussionsupporting
confidence: 85%
“…About 2 weeks after implantation TIGR ® Matrix will gradually become softer and more flexible due to the ongoing degradation in the fast-degrading fiber, unlocking the knitting pattern of the slow-degrading fiber. The slow-degrading fibers keep their mechanics up to 6–9 months and are completely resorbed after ~3 years due to degradation by hydrolysis [18]. …”
Section: Methodsmentioning
confidence: 99%
“…The initial burst strength of the mesh implant as measured according to American Society for Testing and Materials D3787 is above 300 N. This strength is comparable to existing commercially available products that range between 170 and 750 N. More than 50 % of the initial mechanical strength of the mesh, above theoretical and measured values of the highest forces acting on the abdominal wall [8, 9], is maintained during the first 26 weeks, after that the mechanical strength of the mesh is gradually lost [7]. …”
Section: Methodsmentioning
confidence: 82%
“…Following implantation in the abdomen of a sheep model, strong connective tissue was observed after 36 months, with none of the animals showing recurrence at the end of the study. The authors stated that this is the world’s first long-term resorbable mesh and takes a minimum of 6 months to degrade, thereby allowing sufficient time for a collagen matrix to form [67]. Similarly, de Tayrac et al demonstrated that the use of polylactic acid (PLA) could be a promising alternative material for long-lasting pelvic floor repair because of its slower degradation rate, which is attributed to the small fibres.…”
Section: Materials Discussionmentioning
confidence: 99%